Practical database design for industrial maintenance system - Hasan Basari, Abd Samad; Idris, Ariff; Herman, Nanna Suryana (2010)
This paper describes how a database design can play an important role for developing practical industrial maintenance system. The good database design will in return give a better information sharing and good system in term of data accessibility. The design of the database are presented and illustrated by a case. The preliminary result presented to show that is possible to access a more correct view of the situation in the system development and thereby obtain a better base for making maintenance decisions. The database supports the development of applications e.g. for monitoring the performance of a maintenance in the production, for deciding the most appropriate maintenance policy or for simulating possible maintenance solutions.